Mechanisms of Resistance to Noncovalent Bruton’s Tyrosine Kinase Inhibitors - Wang, Eric; Mi, Xiaoli; Thompson, Meghan C; Montoya, Skye; Notti, Ryan Q; Afaghani, Jumana; Durham, Benjamin H; Penson, Alex; Witkowski, Matthew T; Lu, Sydney X; Bourcier, Jessie; Hogg, Simon J; et al. (The New England journal of medicine, 2022)
In nine patients with chronic lymphocytic leukemia that responded to the noncovalent BTK inhibitor pirtobrutinib and then developed resistance, analysis revealed a number of new mutations in the BTK kinase domain and occasional mutations in downstream PLCγ2. Despite the inactivity of BTK, alternative pathways of B-cell–receptor signaling were evident.